First principles study on the structural stability and optoelectronic properties of InxGa1−xAs materials with different Indium component. (26th January 2018) - Shen, Yang; Yang, Xiaodong; Bian, Yue; Liu, Songmin; Tang, Kun; Zhang, Rong; Zheng, Youdou; Gu, Shulin
Abstract: The III–V ternary semiconductors In x Ga1− x As (0 ≤ x ≤ 1) have attracted a great deal of interests in electronics and optoelectronics due to their superior transport properties, high-efficiency thermoelectric applications and so on. In this work, the optoelectronic properties of bulk In x Ga1− x As materials and the phase transition of In x Ga1− x As nanowires (NWs) at different Indium (In) component have been investigated by first-principles calculation using density functional theory. Different calculation models have been chosen to simulate the (2 × 2 × 1) supercells of pure bulk In x Ga1− x As structures and the most stable one has been adopted for further calculation. NWs models of In0.25 Ga0.75 As and In0.75 Ga0.25 As have been employed to represent the In-rich and Ga-rich structures, respectively. Our calculation results have clearly shown that the In-rich nanostructure show more zinc-blende characteristic while the wurtzite phase exhibit dominating role in the Ga-rich NWs. The band gap of bulk models decreases with increasing the In component, which is well consistent with the theoretical formula. With the In component increasing, the lower valence band shifts toward high energy region and the peak value increases, while the absorption edge and peak value move to lower energy side and the static dielectric constant increases. The metal reflective properties emerge in certain photon energy range. Our results offer the guidance to make use of the different properties of In x Ga1− x As materials at different In component.